Interpretation in Understanding the Holy Qur’an: Its Foundations, Methodological Guidelines, and Impact on Meaning Construction - Sabiha Al-Qadhafi Ali (Journal of Libyan Academy Bani Walid, 2025)
This study addresses the role of ta’wil (interpretation) in understanding the Holy Qur’an, considering it a key tool for accessing deeper meanings, especially in verses open to multiple interpretations. The research aims to establish the foundations of ta’wil, tracing its origins and development, and clarifying its relationship with tafsir (exegesis). Special focus is given to the methodological guidelines that regulate interpretation and prevent misuse. The study analyzes selected interpretive examples from Islamic tradition in light of linguistic and legal principles. It adopts an analytical and foundational approach that combines conceptual analysis with contextual understanding. The research concludes that, when governed by proper rules, ta’wil serves as an effective means for renewing Qur’anic understanding and engaging with contemporary contexts, while preserving the sanctity and constants of the text.